Changes in Physiological and Biochemical Parameters in Women During the Spontaneous Menstrual Cycle and Following Oral Contraceptives: Physiological and Biochemical Parameters in Women During the Menstrual Cycle - Afridi, Sanodia; Khakwani, Fahmeed; Fida, Najma; Naeem, Samarah; Yahya, Sheherbano; Khan, Ramsha (Pakistan Journal of Health Sciences, 2025)
Oral contraceptive pills (OCPs) are widely used for birth control and management of various gynaecological conditions. While their primary mechanism is to regulate the reproductive cycle, they are known to exert broader systemic effects. However, comparative data on physiological, hormonal, and metabolic parameters between OCP users and women with natural menstrual cycles remain limited. Objectives: To evaluate and compare selected physiological signs, reproductive hormones, and metabolic indicators among women experiencing natural menstrual cycles and those on OCPs. Methods: A comparative cross-sectional study was conducted involving 80 women aged 18–40 years, divided into two equal groups: natural cycle (n=40) and OCP users (n=40). Data were collected on demographic details, vital signs, and laboratory measures including estrogen, progesterone, LH, FSH, SHBG, TSH, testosterone, HDL cholesterol, and fasting glucose. Statistical analysis was performed using SPSS version 26.0. Results: Significant differences were observed in estrogen, progesterone, LH, and SHBG levels, with OCP users showing notably altered hormonal profiles. OCP users also had higher systolic blood pressure and HDL cholesterol, while glucose levels were slightly elevated. No significant differences were found in prolactin, FSH, or haemoglobin. Conclusions: It was concluded that OCP use is associated with measurable changes in several physiological, hormonal, and metabolic parameters. These findings highlight the importance of routine monitoring in long-term users and support individualized contraceptive counselling based on clinical risk profiles.